Analisis faktor kinerja karyawan pada perusahaan donat : (Studi kasus di Desa Sandik Kecamatan Batulayar Kabupaten Lombok Barat) - Any Tsalasatul Fitriyah; Irma Suriyani Savitri (Journal of Enterprise and Development (JED), 2020)
The objective of this study was to ascertain the elements affecting employee performance. The performance management quality component becomes the driving force behind a company's development and progress. However, only a few things are motivating people to increase their performance. The investigation in this study used exploratory factor analysis (EFA), which is used to reduce the original variable to a variate (factor) in order to determine the dominating factor influencing employee performance. The findings revealed two variables that influence employee performance. These two variables account for up to 74.695 percent of the variation in variables affecting employee performance. The first element makes a sizable contribution (52.478 percent), whereas the second factor makes up the difference. The first factor, organizational support, is comprised of the award factor, the delegating factor, the supervisor's support factor, the employee welfare factor, the working environment factor, and the selling factor. The second aspect is individual competency, which is composed of the skill, motive, character, and self-concept factors.